Impact of Apple Pomace Powder on Fish Finger Qualitative Characteristics - Sanjit L; Dipak T (Advances in Aquaculture and Fisheries Management, 2024)
A The goal of the current study was to assess how various concentrations of apple pomace powder (APP) affected the fish finger qualitative attributes. In order to replace fish meat in the formulation, apple pomace powder was added at four different percentages: 0, 2.5, 4.5, and 6.5. Numerous physicochemical characteristics, sensory qualities, emulsion stability, cooking yield, pH, and proximate composition (i.e., crude protein, fat extract, moisture content, and total ash) were examined in the products. As the amount of apple pomace powder was increased, there was a noticeable increase in both emulsion stability and cooking yield. The product's pH, crude protein, moisture, crude fat, and total ash all showed a significantly (p < 0.05) declining tendency as the amount of apple pomace powder added increased.